Halal Tourism Based School Program Development in SMP 2 Selong East Lombok - Susilawati, Endang (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
This study aims to obtain information and discuss about the development of school programs in SMP Negeri 2 Selong-based tourism in East Lombok. Research method used by researcher is research with qualitative approach. In this study as for the subject to be studied in this study are students and also educators at SMP 2 Selong Lombok Timur. Data analysis method used in this research is Analitycal Hierarchy Process (AHP). Analitycal Hierarchy Process is one of the methods used in solving problems that contain many criteria. Results and discussion of SMPN 2 Selong school program development based on halal tourism in East Lombok in the first development program on the implementation of Life Skills education that describes entrepreneurship and creative economy using AHP method. The first criterion of the development of handicraft programs from used materials that are marketed in tourist areas shows that this first criterion has the highest value compared with other criteria. The development of the second program is the development of education programs based on local and global excellence has five criteria where the development of Islamic-themed arts performance program implemented in the area of ​​the highest criteria tourism object.